Analysis of the results of the introduction of the experimental methodology for the integrated development of motor qualities and the assimilation of elements of the technique of young weightlifters 10-12 years - Bugaev, E.; Dzhym, V.; Boltenkova, O. (Slobozhanskyi herald of science and sport, 2018)
Purpose: revealing the influence of the experimental technique on the development of motor qualities and the assimilation of elements of the technique of young weightlifters 10-12 years.